2010
DOI: 10.1103/physreve.81.041302
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the force network in the jamming transition of an isotropically compressed granular packing

Abstract: The jamming transition of an isotropically compressed granular packing is studied by means of molecular dynamics simulations. The system is shown to undergo a critical transition which is analyzed by looking at the topological structure of the force network. At the critical packing fraction there is a sudden growth of the number of polygons in the network. Above the critical packing fraction the number of triangles keeps growing while the number of the rest of polygons is weakly reduced. Then, we prove that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 25 publications
5
88
0
Order By: Relevance
“…Additionally, they reported that the lengths of these chains satisfy an approximately exponential distribution. Arevalo et al [18] examined polygonal structures that underly a forcechain network, which they determined by selecting all inter-particle forces above some threshold. In their numerical simulations, they observed that triangular structures dominate the network near a critical packing fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they reported that the lengths of these chains satisfy an approximately exponential distribution. Arevalo et al [18] examined polygonal structures that underly a forcechain network, which they determined by selecting all inter-particle forces above some threshold. In their numerical simulations, they observed that triangular structures dominate the network near a critical packing fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The general trend is that the force increases with the number of sides of the polygon. The fact that small polygons in the network allocate smaller forces than big polygons was already observed for the compressed system [25,26].…”
Section: Contact Forcesmentioning
confidence: 85%
“…In Fig. 5 a comparison is made between an isotropically compressed system that is jammed [25] (left column) and the tapped samples studied in this work (right column). From the data for the topological distance and the giant component, a different qualitative behavior is revealed for both types of networks.…”
Section: Force Network Relation To Compressed Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the topology of the force networks has been shown very fruitful [18,19] in a static granular packing. The process of jamming in the light of the topology of force networks was studied in [20,21]. Again, the role of loops in the network was proven to be relevant at the transition point, with third-order loops behaving as an order parameter.…”
Section: Introductionmentioning
confidence: 99%